At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
The answer to your question is: Yes.
Now, would you like to actually see the solution ?
First, multiply the quantity out:
(sin + cos)² = sin²(t) + cos²(t) + 2sin(t)cos(t)
You need to know:
==> sin²(any angle) + cos²(the same angle) = 1
==> 2sin(any angle)cos(the same angle) = sin(double the angle)
So the equation becomes:
(sin + cos)² = 1 + sin(2t)
Now, would you like to actually see the solution ?
First, multiply the quantity out:
(sin + cos)² = sin²(t) + cos²(t) + 2sin(t)cos(t)
You need to know:
==> sin²(any angle) + cos²(the same angle) = 1
==> 2sin(any angle)cos(the same angle) = sin(double the angle)
So the equation becomes:
(sin + cos)² = 1 + sin(2t)
[tex](sin\ t+cos\ t)^2=sin^2t+cos^2t+2\cdot sin\ t\cdot cos\ t=1+sin\ 2t[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.